Bilateral Optic Neuropathy: What Facts in a Valsalva’s Maneuver Context? A Case Report - Constant, Sowagnon Thierry Yves; Yves, Ouattara; Epiphane, Kouaï Bi Ta; Béda, Appia Gilles; Kpatchingnin, Koné; Zana, Diabaté; Lliane, Godé (Transactions on Engineering and Computing Sciences, 2023)
Introduction: Repeated Valsalva’s maneuvers can result in severe optic neuropathy. We describe here, for the first time in the literature, a case of blindness related to this mechanism. Observation: This was a young autistic man engaged several times a day in Valsalva’s maneuvers and who presented with a bilateral and rapidly progressive decrease in visual acuity. The anamnesis, the clinical examination and the radiological explorations made it possible to make the diagnosis of bilateral optic neuropathy secondary to these Valsalva’s maneuvers. Discussion: The optic neuropathy occurring during the Valsalva’s maneuver would be the result of three associated mechanisms: abnormalities of the orbital vascularization, ischemia and chronic compression of the optic nerve responsible for an almost total destruction of the optic nerve and source of blindness.